¿Saben los maestros la física que enseñan? - Zalamea Godoy, E.; París, R. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper attempts to report a research carried out in Colombia about the proficiency in mechanics of high school teachers. Based on observations, some judgements and appreciations are made about the teachers' performance and a teaching method proposal is suggested in order to solve the problems which have been identified.